Nasalization: an overview of the notion and research - Butkauskaitė, Edita (Lietuvių kalba, 2010)
Nasalization, treated both from a phonetic and phonological point of view, has a rather long history of research. It was first described in reference to nasal sounds in the 5th century BC. Nowadays it is mostly treated in the context of abundant experimental research into nasal and nasalized sounds and is based on radiographic, electrographic, nasographic, fiberoscopic and aerodynamic data.In traditional phonetic studies a nasalized segment is understood as a sound whose production involves a flow of air through the mouth and nose; nasalization is defined as the production of a sound when the velum is lowered so that some air passes through the nose.Linguistic studies of Lithuanian and other researchers have identified three types of nasalization: nasal vowels, nasalized vowels and nasal consonants. Only about one fourth of world languages have nasal vowels in their inventory and they are treated as individual phonemes. French is one of the few examples of such languages. In linguistic studies such nasalization is also called contrastive. In languages which have no nasal vowels, nasalization occurs next to or between the nasal consonants [m] and [n]. The type of nasalization is referred to as contextual nasalization; their respective sounds are called nasalized vowels. The notion of nasalization also includes nasal consonants, whose production also involves the air escaping through the mouth and nose.Nasalization has been extensively discussed in the studies on phonetics and phonology produced by foreign researchers, especially those investigating English and French. The studies include both theoretical papers and overviews of experimental research focusing on investigating both sound length and quality. In Lithuania investigation into nasalization has only just started.